Analisis Risiko Bahaya dan Upaya Pengendalian Kecelakaan Kerja dengan Metode Hirarki Pengendalian Bahaya pada Area Penambangan Batu Gamping Bukit Karang Putih di PT. Semen Padang, Sumatera Barat - Ilham Yufahmi; RUSLI HAR (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Semen Padang was founded on 18 March 1910 under the name NV Nederlandsch Indische Portland Cement Maatschappid (NV NIPCM) which is the first cement factory in Indonesia. Workers are always faced with various hazards and risks in the workplace that can cause work accidents and occupational diseases. This study aims to determine the risk of harm, determine the likelihood of work accidents and their consequences, and how to carry out the necessary hazard control against these hazards. Hierarchy of hazard control method was used in this study, the level of hazard risk was determined based on the risk matrix table so that the results obtained were 11 hazard parameters with a low risk level, 14 hazard parameters with a medium risk level and 5 hazard parameters with a high risk level.